Rancang Bangun Mesin Crusher Plastik - Muhammad Nur Aslam; Mohammad Miftachul Munir; Rizal Indrawan (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
In this modern era the plastic waste is a waste that is very difficult to recycle because thedecompotion of waste plastic is very difficult, and also the decompotion of waste plastic need a longtime. There are many types of plastic that we use everyday such as plastic bag for food or for bring acup of tea and etc with cheaper price and you can get the pastic bag in every shop or minimarket inIndonesia makes the plastic waste is the most waste produced from house hold and the others.Therefore we need some ways or method to reduce the plastic waste by making a crusher plasticmachine. There are many materials used to make crusher plastic machine. Start from frame ofmachine and stand frame of diesel motor are use U profile with material ASTM A36. ST42 are usedfor tub crusher, pulley, 2 fly wheel, stand of knife, fly wheel cover, top hopper, bottom hopper. ASTMA36 material is used for key of spindle. HSS material is used for knife crusher plastic machine. 3 Vbeltwith rubber canvas material is used for move spindle crusher plastic machine. The method usedto make this machine is reverse engineering which is compare to another crusher plastic machinethat has been sold in. The advantages from this machine is cheaper than another cursher plasticmachine in market, have low power, can slice or crush plastic until 50 kg/h, and dimension of plasticthat has been sliced is 16 mm or 1,6 cm wich is smaller and smoother than another crusher plasticmachine in market. Type of the plastic that can be sliced by using this machine is polypropylenebecause polypropylene has more benefit in economic. The price of polypropylene which sliced ismore expensive than the other type of plastic and the knife of this machine will blunt faster if slicingor crushing another type of plastic